Similarity of feature selection methods: An empirical study across data intensive classification tasks. Issue 10 (15th June 2015) - Dessì, Nicoletta; Pes, Barbara
Highlights We empirically investigated the similarity among feature selection methods. Extensive experiments were carried out across high dimensional classification tasks. We obtained useful insight into the pattern of agreement of eight popular methods.